Síntese de cadeias carbônicas oxigenadas em nuvens moleculares escuras - Silva, Vitor Neves da [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
This work presents a study on the formation routes of oxygenated carbon chains, in the gas-phase, which were observed in dark molecular clouds. Such chains represent the structure of organic compounds and can provide a glimpse into prebiotic conditions in the molecular cloud that gave rise to Earth. The main chemical processes responsible for the formation of carbon chains have not been fully undestood. In this sense, in order to explore the route of formation of oxygenated organic compounds, chemical reactions and their respective rate coefficients were extracted from the literature, considering the physicochemical conditions of dark clouds, as well as the molecular processes that govern the formation of these compounds in cold medium. Finally, the following relative abundancies were calculated in steady-state:CH3 O/CH3 OH, CH3 /C3 O e H2 CCO/CH3 CO+

Este trabalho apresenta um estudo sobre as rotas de formação das cadeias carbônicas oxigenadas, na fase gasosa, que foram observadas em nuvens moleculares escuras. Tais cadeias representam a estrutura dos compostos orgânicos e podem fornecer um vislumbre das condições pré-bióticas na nuvem molecular que deu origem à Terra. Os principais processos químicos responsáveis pela formação das cadeias carbônicas não foram totalmente esclarecidos. Nesse sentido, para construir a rota de formação dos compostos orgânicos oxigenados, foram extraídas da literatura as reações químicas e seus respectivos coeficientes de taxa, Considerando as condições físico- químicas das nuvens escuras, bem como os processos moleculares que regem a formação desses compostos em meios frios. Por último, foram calculadas no estado estacionário as seguintes abundâncias relativas: CH3 O/CH3 OH, CH3 /C3O e H2 CCO/CH3 CO+ .
Oxygenated carbon-chains synthesis in dark molecular clouds
Keywords: Physics; Space sciences; Chemistry; Física; Ciências do espaço; Química